The crosstalk between neuropilin-1 and tumor necrosis factor-α in endothelial cells - Wang, Ying; Wang, Enfeng; Anany, Mohamed; Füllsack, Simone; Huo, Yu Henry; Dutta, Shamit; Ji, Baoan; Hoeppner, Luke H.; Kilari, Sreenivasulu; Misra, Sanjay; Caulfield, Thomas; Vander Kooi, Craig W.; et al. (Frontiers in Cell and Developmental Biology, 2024)
Tumor necrosis factor-α (TNFα) is a master cytokine which induces expression of chemokines and adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), in endothelial cells to initiate the vascular inflammatory response. In this study, we identified neuropilin-1 (NRP1), a co-receptor of several structurally diverse ligands, as a modulator of TNFα-induced inflammatory response of endothelial cells. NRP1 shRNA expression suppressed TNFα-stimulated leukocyte adhesion and expression of ICAM-1 and VCAM-1 in human umbilical vein endothelial cells (HUVECs). Likewise, it reduced TNFα-induced phosphorylation of MAPK p38 but did not significantly affect other TNF-induced signaling pathways, such as the classical NFκB and the AKT pathway. Immunofluorescent staining demonstrated co-localization of NRP1 with the two receptors of TNF, TNFR1 and TNFR2. Co-immunoprecipitation further confirmed that NRP1 was in the same protein complex or membrane compartment as TNFR1 and TNFR2, respectively. Modulation of NRP1 expression, however, neither affected TNFR levels in the cell membrane nor the receptor binding affinities of TNFα. Although a direct interface between NRP1 and TNFα/TNFR1 appeared possible from a protein docking model, a direct interaction was not supported by binding assays in cell-free microplates and cultured cells. Furthermore, TNFα was shown to downregulate NRP1 in a timedependent manner through TNFR1-NFκB pathway in HUVECs. Taken together, our study reveals a novel reciprocal crosstalk between NRP1 and TNFα in vascular endothelial cells.